Significant Spontaneous Pneumomediastinum and Extensive Subcutaneous Emphysema in a COVID-19 Patient - Arianna Gaspari; Francesca Carrieri; Matteo Villani; Elisabetta Bertellini (Reports, 2024)
A 64-year-old man, who had no pre-existing health conditions, was admitted to the intensive care unit due to progressive shortness of breath resulting from COVID-19. Initially, the patient responded to non-invasive mechanical ventilation, which improved his breathing function. However, after six days, his respiratory function worsened significantly, requiring invasive ventilation. Out of nowhere, the person experienced spontaneous pneumomediastinum and extensive subcutaneous emphysema. The next day, a spontaneous pneumothorax occurred and was successfully drained later. It became evident that there was extensive subcutaneous emphysema also. The CT scan of the chest confirmed the presence of spontaneous pneumomediastinum, but it did not have any effect on the patient’s hemodynamics. The physicians performed a bronchoscopy and imaging with a contrast medium, which ruled out any lesions to the trachea or esophagus. No other issues related to the problem were identified during the examination. Unfortunately, microscopic bullae of interstitial emphysema, or micro air leaks, are visible when they are an adequate size on computed tomography. Recent literature and studies not available during the case report have shown that if the Macklin effect is detected on the baseline CT scan, it could predict the occurrence of pneumothorax or pneumomediastinum.